Interpersonal Education - Maria Inés Nin Márquez; Carina Rossa (Nicolaus Copernicus University in Toruń, 2019)
Recent contributions from neuroscience and their implications on school teaching have encouraged openness to new knowledge, to the need for new skills and to the revamping of teaching, placing educational relationship at the centre of everything. The brain has been designed to learn through sharing experiences. The purpose of these pages is hence to see if there is a correlation between mental development and relationality. In that sense, as Chiara Lubich's pedagogy highlights, educational goal is to develop personal identity starting from the encounter with the other. Besides, interpersonal relationships and emotions will help to improve learning. Neuroscience and cognitive neuroscience have demonstrated there is an interconnection between perception, emotion and cognition during school learning. Therefore, we think that valuation of relational and emotional dimensions in education can improve the processes of teaching and learning. In fact, in the last decades, studies and research about human brain function and teaching and learning processes have led to new findings that nowadays are modifying current pedagogy. The progress on science says that interpersonal skills development can improve children's brain development. The relationship with others and other attachment figures is the enabler to allow or inhibit the organisation of neuronal connections, the capability to activate them as a response to stimulus and allow the expression of brain structures genetically determined. This scenario presents the development of prosocial behaviour, which optimise and postulate the capacity for empathy, promoted by Chiara Lubich as behavioural categories of the Art of Love.